A doped rare earth oxide / carbon nanotube functional separator for a battery and a method of manufacturing the same
Patent Information
- Application Number
- CN202610933433.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-26
- Publication Date
- 2026-08-28
AI Technical Summary
然而,现有碳基涂层主要依赖物理限域作用,对多硫化物的化学吸附及催化转化能力有限,难以实现长循环稳定性与高倍率性能的协同提升
Smart Images

Figure CN122659503A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new energy materials and devices technology, specifically relating to a battery-doped rare earth oxide / carbon nanotube functional separator and its preparation method. Background Technology
[0002] Lithium-sulfur (Li-S) batteries are valued for their ultra-high theoretical specific energy (2600 Wh kg). -1 With its advantages such as abundant sulfur resources, low cost, and environmental friendliness, it is considered a highly promising candidate for the next generation of high-energy-density energy storage.
[0003] However, in actual charge-discharge processes, the complex multi-step solid-liquid-solid conversion reaction of the sulfur cathode leads to the shuttle of intermediate products (LiPS) and slow sulfur redox kinetics, resulting in low utilization of active materials and severe capacity decay. The separator, as a key battery component, plays a crucial role in suppressing LiPS shuttle, but conventional commercial separators (such as polypropylene PP) have large pore sizes, making it difficult to effectively block LiPS transmembrane diffusion. Therefore, constructing functional coatings on the separator surface has become an effective improvement solution. Among these, carbon-based materials, due to their excellent conductivity, high specific surface area, and good chemical stability, are widely used as physical barriers and "second current collectors," effectively blocking LiPS diffusion and improving electron conduction efficiency, thus significantly improving battery performance. However, existing carbon-based coatings mainly rely on physical confinement, with limited ability to chemically adsorb and catalytically convert polysulfides, making it difficult to achieve a synergistic improvement in long-cycle stability and high-rate performance.
[0004] Therefore, introducing polar materials as "chemical anchoring points" can further suppress the shuttle effect and improve reaction kinetics by enhancing the adsorption of LiPS and accelerating its reversibility. Thus, developing a composite membrane that synergistically combines physical confinement and chemical anchoring to efficiently suppress polysulfide shuttle through multiple mechanisms is of great significance for promoting the development of high-performance lithium-sulfur batteries. Summary of the Invention
[0005] This invention addresses the shortcomings of existing lithium-sulfur battery functional membranes, which struggle to simultaneously achieve physical barrier, strong chemical adsorption, and efficient catalytic conversion. It provides a battery-grade doped rare-earth oxide / carbon nanotube functional membrane. By controlling the oxygen vacancy concentration in cerium oxide through La doping and working synergistically with the conductive network constructed from carbon nanotubes, the polysulfide shuttle effect can be effectively suppressed, thereby improving the battery's capacity, rate performance, and cycle stability. Furthermore, the fabrication process is simple and easy for large-scale production.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A battery-grade doped rare-earth oxide / carbon nanotube functional separator includes a separator substrate and a functional layer deposited on one side of the separator substrate. The functional layer is composed of lanthanum-doped cerium oxide (La-CeO) with abundant oxygen vacancies. 2-x Lanthanum-doped cerium oxide / carbon nanotube composite material (La-CeO) was obtained by loading hydroxylated carbon nanotubes (CNTs) onto the surface of CNTs. 2-x / CNT) composition; La-CeO 2-x In the CeO2 lattice, La is introduced as a substitution dopant, inducing lattice distortion and forming oxygen vacancies.
[0008] As a preferred technical solution of the present invention, in the battery-doped rare earth oxide / carbon nanotube functional separator:
[0009] The battery separator substrate is one of polypropylene porous membrane, polyethylene porous membrane, polyethylene / polypropylene composite porous membrane, or one of polyimide separator or polyethylene terephthalate-based nonwoven membrane.
[0010] The functional layer in the functional diaphragm has a unit area loading of 0.1~0.3 mg / cm². -2 .
[0011] This invention also proposes a method for preparing a battery-grade doped rare-earth oxide / carbon nanotube functional separator. First, ordinary commercial multi-walled carbon nanotubes are activated to obtain hydroxylated CNTs. Then, using the hydroxylated CNTs as a carrier, CeCl3·7H2O as the Ce source and LaCl3·7H2O as the La source, the mixture is stirred in an alkaline solution system and then calcined at high temperature under an inert atmosphere to obtain La-CeO. 2-x / CNT composite material was then uniformly dispersed and filtered onto one side of a common commercial battery separator substrate to obtain a functional separator for lithium-sulfur batteries.
[0012] As a preferred technical solution of the present invention, the specific steps of the preparation method are as follows:
[0013] (1) Preparation of hydroxylated CNTs: Commercial multi-walled carbon nanotubes were added to 65%~70% concentrated HNO3 and refluxed at 100~140 °C for 4~6 h. After washing and vacuum drying, hydroxylated CNTs were obtained.
[0014] (2) La-CeO 2-xPreparation of CNT composite material: Hydroxylated CNTs were ultrasonically dispersed in deionized water to obtain dispersion A; CeCl3·7H2O and LaCl3·7H2O were dissolved in deionized water at a molar ratio of 9~24:1 to obtain solution B; the mass ratio of hydroxylated CNTs to CeCl3·7H2O was 0.8~1.2:0.8~1.2; solution B was added dropwise to dispersion A and ultrasonically mixed to obtain mixture C, using 0.1~0.5 mol L... -1 The pH was adjusted to 8-12 with NaOH, and the mixture was stirred at room temperature for 24 h. The product was then filtered, washed, and dried to obtain the precursor. The precursor was then calcined in an inert atmosphere at a temperature of 380-500 ℃ with a heating rate of 2-5 ℃ / min. -1 The heat treatment time was 2-4 hours to obtain La-CeO. 2-x / CNT composite material;
[0015] (3) Preparation of lithium-sulfur functional membrane: The La-CeO obtained in step (2) is used as a prestressing membrane. 2-x / CNTs were ultrasonically dispersed in anhydrous ethanol to obtain a dispersion, which was then filtered onto one side of a common commercial battery separator substrate and vacuum dried to obtain a battery-doped rare earth oxide / carbon nanotube functional separator.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0017] This invention uses a conventional commercial battery separator as a substrate, and filters La-CeO on one side of its surface. 2-x / CNT composite material serves as the functional layer. Through La doping-induced oxygen vacancy regulation, strong chemisorption and efficient catalytic conversion of polysulfides are achieved. Carbon nanotubes construct a three-dimensional conductive network, combining physical confinement with rapid electron transport capabilities. The synergistic effect of these two components effectively suppresses the polysulfide shuttle effect, thereby significantly improving the specific capacity, rate performance, and cycle stability of lithium-sulfur batteries. Attached Figure Description
[0018] Figure 1 Preparation of La-CeO in Example 1 2-x (a) SEM image and (b) TEM image of the / CNT composite material.
[0019] Figure 2 Preparation of La-CeO in Examples 1 and 2 2-x / CNT、CeO 2-x (a) XRD pattern of the / CNT composite material and (b) locally magnified XRD pattern of the (111) crystal plane.
[0020] Figure 3 Preparation of La-CeO in Example 1 2-x(a) XPS full spectrum, (b) C 1s, (c) O 1s, (d) La 3d and (e) Ce 3d high-resolution spectra of the / CNT composite material.
[0021] Figure 4 Preparation of CeO in Example 2 2-x (a) XPS full spectrum, (b) C 1s, (c) O 1s and (d) Ce3d high-resolution spectra of the / CNT composite material.
[0022] Figure 5 The results of constant current charge-discharge cycle tests at a 0.5 C rate are shown for the lithium-sulfur battery prepared in Example 1.
[0023] Figure 6 The results show the performance test results of the lithium-sulfur battery prepared in Example 1 at different rates.
[0024] Figure 7 The results of constant current charge-discharge cycle tests at 0.5 C rate for the lithium-sulfur battery prepared for Comparative Example 1 are shown.
[0025] Figure 8 The results show the performance of the lithium-sulfur battery prepared in Comparative Example 1 at different rates. Detailed Implementation
[0026] The following detailed description, in conjunction with embodiments and accompanying drawings, provides a battery-grade doped rare-earth oxide / carbon nanotube functional separator and its preparation method.
[0027] Example 1
[0028] This embodiment provides a method for preparing a doped rare-earth oxide / carbon nanotube functional separator for batteries, and the specific steps are as follows:
[0029] (1) Preparation of hydroxylated CNTs: Commercial multi-walled carbon nanotubes were added to 68% concentrated HNO3, refluxed at 120 °C for 4 h, washed and vacuum dried to obtain hydroxylated CNTs;
[0030] (2) La-CeO 2-x Preparation of CNT composite material: 100 mg of hydroxylated CNTs were ultrasonically dispersed in deionized water to obtain dispersion A; 100 mg of CeCl3·7H2O and 11 mg of LaCl3·7H2O (molar ratio 9:1) were dissolved in deionized water to obtain solution B; solution B was added dropwise to dispersion A and ultrasonically mixed to obtain mixture C. A 0.1 mol / L solution was then prepared. -1 The pH was adjusted to 10 with NaOH, and the mixture was stirred at room temperature for 24 h. The product was then filtered, washed, and dried to obtain the precursor. The precursor was then calcined in an argon atmosphere at a temperature of 400 ℃ and a heating rate of 5 ℃ / min. -1The heat treatment time was 2 hours to obtain La-CeO. 2-x / CNT composite material;
[0031] (3) Preparation of lithium-sulfur functional membrane: The La-CeO obtained in step (2) is used as a prestressing membrane. 2-x / CNTs were ultrasonically dispersed in anhydrous ethanol to obtain a dispersion. This dispersion was then filtered onto one side of a standard commercial battery PP separator substrate (Celgard 2500), and vacuum dried to obtain a battery-grade doped rare-earth oxide / carbon nanotube functional separator. The functional layer (La-CeO) 2-x The area loading of the CNT composite material is 0.18 mg / cm². -2 The thickness is 5 µm.
[0032] Please see Figure 1 The figure shows the preparation of La-CeO in this embodiment. 2-x (a) SEM image and (b) TEM image of the / CNT composite material. As shown in the figures, the carbon nanotubes intertwine to form a conductive network, which can both physically block the migration of polysulfides and construct continuous electron transport channels. La-CeO 2-x Nanoparticles with a diameter of approximately 5 nm and uniformly loaded on the surface of hydroxylated CNTs can efficiently adsorb and catalyze the conversion of polysulfides that migrate to the membrane surface, thereby inhibiting the polysulfide "shuttle effect".
[0033] Please see Figure 2 , by La-CeO 2-x / CNT and CeO 2-x From the XRD pattern (a) and the magnified XRD pattern (b) of the (111) crystal plane of the / CNT composite material, it can be seen that La-CeO 2-x / CNT and CeO 2-x The XRD patterns of the La-CeO2 composite material all matched the characteristic peaks of the XRD pattern in the standard card (JCPDS No. 00-034-0394), indicating that La doping did not change the CeO2 crystal structure. Furthermore, La-CeO2... 2-x No characteristic peaks of elemental La were observed in the XRD pattern of the / CNT composite material, indicating that La enters the CeO2 lattice in an atomic-level manner. 2-x Compared to / CNT, La-CeO 2-x The small-angle shift of the (111) diffraction peak of / CNT indicates that the composite material exhibits lattice distortion.
[0034] Please see Figure 3 The figure shows the preparation of La-CeO in this embodiment. 2-x(a) XPS full spectrum, (b) C1s, (c) O 1s, (d) La 3d and (e) Ce 3d high-resolution spectra of the / CNT composite material. Figure 3 (a) It can be known that La-CeO 2-x / CNT composite materials contain four elements: La, C, Ce, and O; such as Figure 3 As shown in (b), three characteristic peaks exist in the high-resolution spectrum of C 1s: CC / C=C bond (284.4 eV), CO bond (285.7 eV), and C=O bond (289.6 eV); Figure 3 As shown in (c), in the high-resolution spectrum of O 1s, the characteristic peaks at 529.9 eV, 532.1 eV, and 533.9 eV correspond to lattice oxygen, oxygen vacancies, and adsorbed oxygen, respectively. Calculations based on peak area integration show that the La-CeO in Example 1... 2-x The relative oxygen vacancy content of / CNT is approximately 46%, while in Example 2, CeO 2-x The corresponding value of / CNT is approximately 37%, indicating that La doping significantly increases the oxygen vacancy concentration. This quantitative result, together with the small-angle shift of the (111) diffraction peak in XRD, confirms that La doping induces lattice distortion and oxygen vacancy generation. Figure 3 As shown in (d), in the high-resolution spectrum of La 3d, the characteristic peaks with binding energies at 834.4 eV and 839.1 eV are attributed to La 3d. 5 / 2 The characteristic peaks at 851.6 eV and 861 eV correspond to La 3d orbitals. 3 / 2 The orbitals indicate that lanthanum's valence state is close to +3, with La content approximately 2.1 wt%. Figure 3 As shown in (e), in the high-resolution spectrum of Ce3d, the characteristic peaks at 882.8 eV, 889.7 eV, 898.9 eV, 901.4 eV, 907.9 eV, and 917.4 eV correspond to CeO. 2-x Ce 4+ The characteristic peaks at 885.7 eV and 904.6 eV correspond to CeO. 2-x Ce 3+ The characteristic peaks of La-CeO₂ were observed. XPS results showed that La-CeO₂... 2-x The presence of numerous oxygen vacancies in CNTs enhances their chemisorption capacity and catalytic conversion activity for polysulfides, thereby effectively suppressing the shuttle effect and improving the utilization rate of active sulfur.
[0035] Table 1 La-CeO 2-x / CNT composite material inductively coupled plasma-mass spectrometry (ICP-MS) test results
[0036] element La Ce Content (wt%) 2.1 47.9
[0037] La-CeO prepared in this embodiment 2-x A 2032 coin cell was assembled using a CNT functional separator, a carbon / sulfur composite positive electrode, a lithium metal negative electrode, and a 1,3-dioxolane (DOL) / ethylene glycol dimethyl ether (DME)-based lithium di(trifluoromethanesulfonic acid)imide (LiTFSI) electrolyte, following the sequence of negative electrode shell-spring sheet-gasket-lithium sheet-electrolyte-separator-electrolyte-positive electrode sheet-positive electrode shell. Electrochemical performance was then tested. The areal mass of active sulfur in the positive electrode sheet was approximately 1.5 mg cm⁻¹. -2 .
[0038] Please see Figure 5 The figure shows the constant current charge-discharge test of the lithium-sulfur battery prepared in Example 1 at 0.5 C. As can be seen from the figure, the initial discharge specific capacity is as high as 1205.9 mAh g. -1 After 500 charge-discharge cycles, the capacity decreased to 766.7 mAh g. -1 The average capacity decay rate per revolution is approximately 0.073%.
[0039] Please see Figure 6 The figure shows the rate performance test results of the lithium-sulfur battery prepared in Example 1. The reversible capacities were 1420.7, 1208.5, 1064.5, 892.4, 763.3, and 674.2 mAhg after charge-discharge cycles of 0.2, 0.5, 1, 2, 3, and 5 C, respectively. -1 .
[0040] Comparative Example 1
[0041] To illustrate the La-CeO provided in this invention in a comparative manner 2-x The influence of CNT functional separator on the electrochemical performance of lithium-sulfur batteries: The preparation of lithium-sulfur batteries in Comparative Example 1 is basically the same as that in Example 1, except that batteries are assembled and charged and discharged using ordinary commercial battery PP separator substrate (Celgard 2500).
[0042] Please see Figure 7 The figure shows the constant current charge-discharge test of the lithium-sulfur battery prepared in Comparative Example 1 at 0.5 C. As can be seen from the figure, the initial discharge specific capacity is as high as 905.4 mAh g⁻¹. -1 After 500 charge-discharge cycles, the capacity decreased to 378.6 mAh g. -1 The average capacity decay rate per cycle was approximately 0.116%. Compared to Example 1, the lithium-sulfur battery using the Celgard 2500 separator in Comparative Example 1 showed a decrease in both specific capacity and cycle stability.
[0043] Please see Figure 8The figure shows the rate performance test results of the lithium-sulfur battery in Comparative Example 1. The reversible capacities were 824.3, 619.8, 497.8, 405.7, 359, and 299.5 mAh g⁻¹, respectively, after charge-discharge cycles of 0.2, 0.5, 1, 2, 3, and 5 C. -1 Its rate performance is significantly lower than that of the lithium-sulfur battery assembled using a functional separator in Example 1.
[0044] Example 2
[0045] The preparation method in this embodiment is the same as in Example 1, except that no La source is added in step (2). All other experimental conditions are the same, and CeO with a low oxygen vacancy concentration is obtained. 2-x / CNT functional diaphragm.
[0046] Please see Figure 4 The figure shows the preparation of CeO in this embodiment. 2-x (a) XPS full spectrum, (b) C 1s, (c) O 1s, and (d) Ce 3d high-resolution spectra of the / CNT composite material. Figure 4 (a) It can be known that CeO 2-x / CNT composite materials contain three elements: C, Ce, and O; such as Figure 4 As shown in (b), three characteristic peaks exist in the high-resolution spectrum of C 1s: CC / C=C bond (284.9 eV), CO bond (285.6 eV), and C=O bond (289.3 eV); Figure 4 As shown in (c), in the high-resolution spectrum of O 1s, the characteristic peaks at 530 eV, 532 eV, and 533.9 eV correspond to lattice oxygen, oxygen vacancies, and adsorbed oxygen, respectively. Figure 4 As shown in (d), in the high-resolution spectrum of Ce3d, the characteristic peaks at 883 eV, 889.8 eV, 899.2 eV, 901.6 eV, 908.2 eV, and 917.5 eV correspond to CeO. 2-x Ce 4+ The characteristic peaks at 886.1 eV and 904 eV correspond to CeO. 2-x Ce 3+ The characteristic peaks of CeO₂ were observed. XPS results showed that CeO₂... 2-x The oxygen vacancy concentration in CNTs was significantly lower than that in La-CeO. 2-x / CNT.
[0047] Compared with Example 1, the CeO prepared in this example 2-x The electrochemical performance of the lithium-sulfur battery assembled with the CNT functional separator, including discharge capacity, rate capability, and cycle stability, was significantly lower than that of Example 1: the initial discharge capacity at 0.5 C was 1150.8 mAh g⁻¹.-1 After 500 charge-discharge cycles, the capacity decreased to 690.3 mAh g. -1 The average capacity decay rate per revolution is approximately 0.080%.
[0048] Example 3
[0049] The preparation method in this embodiment is the same as in Embodiment 1, except that in step (3), La-CeO is filtered onto the surface of a common commercial battery PP separator substrate (Celgard 2500). 2-x / CNT load per unit area is 0.1 mg cm⁻¹ -2 The functional layer thickness was 4 µm, and all other experimental conditions were the same.
[0050] Compared with Example 1, the La-CeO prepared in this example 2-x The electrochemical performance of the lithium-sulfur battery assembled with the CNT functional separator, including discharge capacity, rate capability, and cycle stability, was significantly lower than that of Example 1: the initial discharge capacity at 0.5 C was 1169.4 mAh g⁻¹. -1 After 500 charge-discharge cycles, the capacity decreased to 710.8 mAh g. -1 The average capacity decay rate per revolution is approximately 0.078%.
[0051] Example 4
[0052] The preparation method in this embodiment is the same as in Example 1, except that the molar ratio of CeCl3·7H2O to LaCl3·7H2O in step (2) is adjusted to 24:1, while other implementation conditions remain unchanged, thus preparing La-CeO 2-x / CNT functional diaphragm.
[0053] Compared with Example 1, the La-CeO prepared in this example 2-x The electrochemical performance of the lithium-sulfur battery assembled with the CNT functional separator, including discharge capacity, rate capability, and cycle stability, was significantly lower than that of Example 1: the initial discharge capacity at 0.5 C was 1121.3 mAh g⁻¹. -1 After 500 charge-discharge cycles, the capacity decreased to 633.5 mAh g. -1 The average capacity decay rate per revolution is approximately 0.087%.
[0054] Example 5
[0055] The preparation method in this embodiment is the same as in Example 1, except that the molar ratio of CeCl3·7H2O to LaCl3·7H2O in step (2) is adjusted to 15:1, while other implementation conditions remain unchanged, thus preparing La-CeO 2-x / CNT functional diaphragm.
[0056] Compared with Example 1, the La-CeO prepared in this example 2-x The electrochemical performance of the lithium-sulfur battery assembled with the CNT functional separator, including discharge capacity, rate capability, and cycle stability, was significantly lower than that of Example 1: the initial discharge capacity at 0.5 C was 1168.4 mAh g⁻¹. -1 After 500 charge-discharge cycles, the capacity decreased to 706.9 mAh g. -1 The average capacity decay rate per revolution is approximately 0.079%.
[0057] Example 6
[0058] The preparation method in this embodiment is the same as in Example 1, except that the calcination temperature in step (2) is 200 °C, while all other conditions remain unchanged, to prepare La-CeO. 2-x / CNT functional diaphragm.
[0059] Compared with Example 1, the La-CeO prepared in this example 2-x The electrochemical performance of the lithium-sulfur battery assembled with the CNT functional separator, including discharge capacity, rate capability, and cycle stability, was significantly lower than that of Example 1: the initial discharge capacity at 0.5 C was 1101.6 mAh g⁻¹. -1 After 500 charge-discharge cycles, the capacity decreased to 600.3 mAh g. -1 The average capacity decay rate per cycle was approximately 0.091%. This indicates that insufficient calcination temperature led to inadequate cerium oxide crystallization and insufficient oxygen vacancy formation, thereby weakening the catalytic conversion ability of polysulfides.
[0060] The above description is merely an example and illustration of the concept of the present invention. Any modifications or additions made by those skilled in the art to the specific embodiments described, or any substitutions made in a similar manner, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, shall fall within the protection scope of the present invention.
Claims
1. A battery-grade doped rare-earth oxide / carbon nanotube functional separator, characterized in that, It includes a membrane substrate and a functional layer deposited on one side of the membrane substrate, wherein the functional layer is composed of lanthanum-doped cerium oxide (La-CeO) with abundant oxygen vacancies. 2-x Lanthanum-doped cerium oxide / carbon nanotube composite material (La-CeO) loaded on the surface of hydroxylated carbon nanotubes (CNTs) 2-x / CNT) composition; La-CeO 2-x La elements enter the CeO2 lattice through substitution doping, causing lattice distortion and inducing the generation of oxygen vacancies.
2. The battery-grade doped rare-earth oxide / carbon nanotube functional separator as described in claim 1, characterized in that, The membrane substrate is one of polypropylene porous membrane, polyethylene porous membrane, polyethylene / polypropylene composite porous membrane, or one of polyimide membrane or polyethylene terephthalate-based nonwoven membrane.
3. The battery-grade doped rare-earth oxide / carbon nanotube functional separator as described in claim 1, characterized in that, The functional layer in the functional diaphragm has a unit area loading of 0.1~0.3 mg / cm². -2 .
4. The method for preparing the battery-use doped rare-earth oxide / carbon nanotube functional separator according to any one of claims 1 to 3, characterized in that, First, commercially available multi-walled carbon nanotubes were activated to prepare hydroxylated CNTs. Then, using hydroxylated CNTs as a carrier, CeCl3·7H2O as the Ce source and LaCl3·7H2O as the La source, the mixture was stirred in an alkaline solution system and then calcined at high temperature under an inert atmosphere to obtain La-CeO. 2-x / CNT composite material was then uniformly dispersed and filtered onto one side of a common commercial battery separator substrate to obtain a functional separator for lithium-sulfur batteries.
5. The preparation method according to claim 4, characterized in that, The specific preparation steps are as follows: (1) Preparation of hydroxylated CNTs: Commercial multi-walled carbon nanotubes were added to 65%~70% concentrated HNO3 and refluxed at 100~140 °C for 4~6 h. After washing and vacuum drying, hydroxylated CNTs were obtained. (2) La-CeO 2-x Preparation of CNT composite material: Hydroxylated CNTs were ultrasonically dispersed in deionized water to obtain dispersion A; CeCl3·7H2O and LaCl3·7H2O were dissolved in deionized water at a molar ratio of 9~24:1 to obtain solution B; the mass ratio of hydroxylated CNTs to CeCl3·7H2O was 0.8~1.2:0.8~1.2; solution B was added dropwise to dispersion A and ultrasonically mixed to obtain mixture C, using 0.1~0.5 mol L... -1 The pH was adjusted to 8-12 with NaOH, and the mixture was stirred at room temperature for 24 h. The product was then filtered, washed, and dried to obtain the precursor. The precursor was then calcined in an argon atmosphere at a temperature of 380-500 ℃ and a heating rate of 2-5 ℃ / min. -1 The heat treatment time was 2-4 hours to obtain La-CeO. 2-x / CNT composite material; (3) Preparation of lithium-sulfur functional membrane: The La-CeO obtained in step (2) is used as a prestressing membrane. 2-x / CNTs were ultrasonically dispersed in anhydrous ethanol to obtain a dispersion, which was then filtered onto one side of a commercial battery separator substrate and vacuum dried to obtain a battery-doped rare earth oxide / carbon nanotube functional separator.